Atomically resolved imaging of radiation-sensitive metal-organic frameworks via electron ptychography - Li, Guanxing; Xu, Ming; Tang, Wen-Qi; Liu, Ying; Chen, Cailing; Zhang, Daliang; Liu, Lingmei; Ning, Shoucong; Zhang, Hui; Gu, Zhi-Yuan; Lai, Zhiping; Muller, David A.; et al. (Nature communications, 2025)
Electron ptychography, recognized as an ideal technique for low-dose imaging, consistently achieves deep sub-angstrom resolution at electron doses of several thousand electrons per square angstrom (e − /Å 2 ) or higher. Despite its proven efficacy, the application of electron ptychography at even lower doses—necessary for materials highly sensitive to electron beams—raises questions regarding its feasibility and the attainable resolution under such stringent conditions. Herein, we demonstrate the implementation of near-atomic-resolution ( ~ 2 Å) electron ptychography reconstruction at electron doses as low as ~100 e − /Å 2 , for metal-organic frameworks (MOFs), which are known for their extreme sensitivity. The reconstructed images clearly resolve organic linkers, metal clusters, and even atomic columns within these clusters, while unravelling various local structural features in MOFs, including missing linkers, extra clusters, and surface termination modes. By combining the findings from simulations and experiments, we have identified that employing a small convergence semi-angle during data acquisition is crucial for effective iterative ptychographic reconstruction under such low-dose conditions. This important insight advances our understanding of the rapidly evolving electron ptychography technique and provides a novel approach to high-resolution imaging of various sensitive materials. This study investigates optimal 4D-STEM data acquisition parameters for low-dose electron ptychography, achieving near-atomic-resolution ( ~ 2 Å) reconstruction at electron doses of ~100 e − /Å 2 on highly sensitive metal-organic framework materials.